MATHEMATICALLY UNIVERSALIZED ESTIMATIONS OF MEDICAL RESULTS - Vesić, Nenad O.; Maćukanović-Golubović, Lana; Ilić, Dušica (Matematichki Bilten, 2017)
The methodology of medical-data-analysis is improved here. Three novel computational algorithms for medical data analysis are presented in this paper. The first of them analyzes a state of single patient. The second algorithm analyzes a status of group of patients based on states of single patients from this group. The third algorithm compares previously analyzed effects of different groups of patients. Measure characteristics of results of the first algorithm are examined.